Breaking the Taboo: The Role of Visual Metaphors in Reshaping Profanity in Online Communication - Xiaofei Zhao; Jinlin Wang (International Journal of Education and Humanities, 2025)
This study explores the transformation of Chinese profanities into visual symbols within internet culture, specifically examining the metaphorical processes through which offensive language is reinterpreted as socially acceptable symbols. The research addresses the gap in existing literature by applying Conceptual Metaphor Theory and Multimodal Metaphor Theory to understand how profanities, such as the term “操” (cào), are metaphorically mapped onto non-offensive symbols, like “草” (cǎo) and plant emojis. The study investigates two key questions: (1) How do profanities transform into visual symbols through metaphorical mappings? and (2) How do multimodal metaphors, combining text and images, reinforce or diminish the original meaning of these profanities? Using a qualitative approach, the paper identifies three core metaphorical mechanisms: phonetic metaphors, imagery metaphors, and metonymic substitution. The findings reveal that visual metaphors play a crucial role in bypassing censorship, retaining emotional intensity, and facilitating social communication in digital spaces. The study’s theoretical contribution includes extending Conceptual Metaphor Theory to visual and multimodal symbols and proposing a “three-stage transformation” model (language symbol → multimodal mapping → cultural appropriation). This research provides insights into the cognitive, cultural, and social processes behind the evolution of language in the digital age and suggests that visual metaphors offer a powerful tool for reshaping online communication within cultural and censorship constraints